2016
DOI: 10.1097/inf.0000000000000996
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Molecular Epidemiology of Childhood Invasive Nontypeable Haemophilus influenzae Disease in England and Wales

Abstract: The high level of genetic diversity in invasive NTHi strains highlights the difficulties in developing an effective vaccine against this pathogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 42 publications
1
26
0
1
Order By: Relevance
“…Higher H. influenzae notification rates for infants, particularly neonates, the elderly, and women of childbearing age, were described before ( 30 , 31 ) and after ( 32 34 ) the introduction of routine Hib vaccination. In addition, several studies showed an increased burden of NTHi in groups more susceptible to infection, with high proportions of intensive care admission, high case-fatality rates, and frequent sequelae among survivors ( 2 , 29 , 32 , 35 ). The notification rate of NTHi cases in infants <1 month of age, with most cases presenting as septicemia, is particularly striking.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Higher H. influenzae notification rates for infants, particularly neonates, the elderly, and women of childbearing age, were described before ( 30 , 31 ) and after ( 32 34 ) the introduction of routine Hib vaccination. In addition, several studies showed an increased burden of NTHi in groups more susceptible to infection, with high proportions of intensive care admission, high case-fatality rates, and frequent sequelae among survivors ( 2 , 29 , 32 , 35 ). The notification rate of NTHi cases in infants <1 month of age, with most cases presenting as septicemia, is particularly striking.…”
Section: Discussionmentioning
confidence: 99%
“…It is probable that the number of NTHi infections among neonates is underestimated ( 37 ), although the increasing notification rate among infants <1 month of age indicates that reporting may be improving. If developed, a vaccine against NTHi that could be administered to pregnant women could provide protection to expectant mothers and neonates ( 35 ). The genetic diversity of NTHi complicates vaccine development, but exploration into potential NTHi vaccine candidates is ongoing ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To the best of our knowledge, this is the first reported case of a bloodstream infection with S. pneumoniae and H. influenzae in a previously healthy child. Both bacterial pathogens are generally responsible for monomicrobic bloodstream infections, with severity varying from mild to fatal depending on the patient's history . We could not determine the reason for the two bacterial strains of bacteremia, but it is possible that both type 19A serotype S. pneumoniae and NTHi could be the pathogens involved, because the PCV7 vaccine covers only serotypes 4, 6B, 9V, 14, 18C, 19F, 23F, not including 19A, and Hib conjugate vaccine covers only serotype b.…”
Section: Discussionmentioning
confidence: 99%